Potent Cytotoxicity of Four Cameroonian Plant Extracts on Different Cancer Cell Lines - Ahmed Somaida; Imran Tariq; Ghazala Ambreen; Ahmed Mohamed Abdelsalam; Abdallah Mohamed Ayoub; Matthias Wojcik; Jean Paul Dzoyem; Udo Bakowsky (MDPI AG, 2020)
In this study, the potential cytotoxicity of four plant extracts originated from Cameroon: Xylopia aethiopica (XA), Imperata cylindrica (IC), Echinops giganteus (EG) and Dorstenia psilurus (DP) were examined in vitro. We tested the anti-proliferative activity of the methanolic extracts of these compounds using MTT assay on seven different human cancer cell lines: HeLa, MDA-MB-231, A549, HepG2, U-87, SK-OV-3 and HL60. Induction of cell death was assessed by cell cycle analysis, apoptosis was determined by Annexin V-FITC binding and caspase 3/7 activity. As well, changes in mitochondrial membrane potential (MMP) and cell migration were tested. The genetic toxicity, using the alkaline comet assay, was evaluated. The studied extracts inhibited the cell proliferation of all tested cancer cell lines with concentration dependent effect over time. All of these extracts mainly induced apoptosis of HeLa cells by the accumulation of hypodiploid cells in the sub-G0/G1 phase and increasing the activity of caspase 3/7, as well they showed potential MMP disturbance and expressed a marked inhibitory effect on cell migration. Assessment of probable genetic toxicity by these extracts revealed no or minimum incidence of genetic toxicity. Therefore, the studied plant extracts are exhibiting potent anticancer activity based upon marked induction of tumor-cell death.